2006
DOI: 10.1021/es0524144
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate Addition Increases Methylmercury Production in an Experimental Wetland

Abstract: Atmospheric mercury is the dominant Hg source to fish in northern Minnesota and elsewhere. However, atmospherically derived Hg must be methylated prior to accumulating in fish. Sulfate-reducing bacteria are thought to be the primary methylators of Hg in the environment. Previous laboratory and field mesocosm studies have demonstrated an increase in methylmercury (MeHg) levels in sediment and peatland porewaters following additions of sulfate. In the current ecosystem-scale study, sulfate was added to half of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
149
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(154 citation statements)
references
References 41 publications
5
149
0
Order By: Relevance
“…Methylmercury concentrations are higher (e.g., Bodaly et al 1993) and pH (e.g., Eilers et al 1983) and abundance of forage fish (e.g., Piper et al 2012) are lower in smaller than in larger lakes, which likely explains why reproductive success in this study was lower in smaller than in larger lakes. Also, methylmercury concentrations are higher where pH is lower (e.g., Jeremiason et al 2006), which combined with the direct negative effects of low pH on food supply, likely explains why reproductive success in this study was lower where pH was lower.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Methylmercury concentrations are higher (e.g., Bodaly et al 1993) and pH (e.g., Eilers et al 1983) and abundance of forage fish (e.g., Piper et al 2012) are lower in smaller than in larger lakes, which likely explains why reproductive success in this study was lower in smaller than in larger lakes. Also, methylmercury concentrations are higher where pH is lower (e.g., Jeremiason et al 2006), which combined with the direct negative effects of low pH on food supply, likely explains why reproductive success in this study was lower where pH was lower.…”
Section: Discussionmentioning
confidence: 76%
“…The amount of methylmercury in lake water available to enter food chains is governed by multiple biotic and abiotic methylation and demethylation pathways; thus, uptake is greatest where the methylation rate exceeds the demethylation rate (Celo et al 2006). Sulfur oxides from acid precipitation favor methylation because they increase the activity of sulfur-reducing bacteria, which convert large amounts of mercury to methylmercury (Jeremiason et al 2006). Higher water temperatures also increase the activity of the bacteria and favor methylation over demethylation (Shin and Krenkel 1976, Wright and Hamilton 1982, Ramlal et al 1993.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KruskalWallis test confirmed that watersheds with mining as prevalent activities had significantly higher (p\0.05) concentrations of sulfate than the other identified land-use types. Although both sulfate and organic matter can stimulate microbial methylation of ionic Hg (Jeremiason et al 2006), they also do have optimum values beyond which Hg methylation becomes limited due to reduced Hg bioavailability through both binding to organic ligands and precipitation as insoluble Hg sulfide minerals. Finally, agricultural and urban activities within the MARB could impact MeHg production/accumulation in sediments through nutrient inputs as reported for other watersheds by Balogh et al (2002Balogh et al ( , 2003.…”
Section: Resultsmentioning
confidence: 99%
“…The Hg complexation in the mixtures was then investigated. The Hg species distribution plotted against salinity content (‰) in the mixtures is shown , is the parameter that triggers the production of MeHg (Bates et al, 2002;Jeremiason et al, 2006;Wang et al, 2009;Weaver et al, 2008;Wnalin et al, 2007). In order to understand the water quality conditions that favor the complexation between Hg and Sulfur, which can lead to the methylation of Hg, the Hg species distribution at various redox values in ENP water was evaluated (using the water quality data at P33 station, which is shown in Table 50); the results are depicted in Figure 72.…”
Section: Sensitivity To Salinity On Inorganic Hg Speciationmentioning
confidence: 99%